PS01.198: THERAPEUTIC STRATEGY FOR ONCOLOGIC EMERGENCY IN ESOPHAGEAL CANCER. (14th September 2018) - Fujita, Junki; Muroi, Hiroto; Nakajima, Masanobu; Yamaguchi, Satoru; Sasaki, Kinro
Abstract: Background: Oncologic emergency in esophageal cancer are classified into bleeding, fistula and stenosis. The esophageal cancer infiltrating surrounding organs is inoperable. Although chemoradiotherapy is often used to cure advanced esophageal cancer with invasion to other organs, the prognosis is generally poor. In this study, we investigated and assessed the outcomes of esophageal stent, bypass surgery and salvage surgery in advanced esophageal cancer with aortic invasion, combined with aortic stent-graft. Methods: 24 patients who received esophageal stent, 6 patients who received bypass surgery and 4 patients who underwent salvage surgery at the Dokkyo Medical University Hospital between April 2009 and December 2016 were reviewed retrospectively. Results: The esophageal stent was performed for stenosis in 15 cases, airway fistula in 4 cases, lung fistula in 4 cases and mediastinal fistula in 1 case. Although oral intake improved in 21/24 cases (87.5%), all stenosis cases achieved to gain oral intake. On the other hand, the bypass surgery group achieved to gain oral intake in all cases. The days required to start oral intake in the stent group were significantly shorter than that of the bypass group ( P  < 0.05). The same results was obtained in the hospitalization ( P  < 0.05). In the salvage surgery group, the average operative duration was 580 min (range, 307–825 min), the average blood loss was 543ml (range, 194–914ml) and the average hospitalization was 32days (range, 15–47days). There were no postoperative complications and all cases have been achieved pathological complete response. Conclusion: Even for advanced esophageal cancer needed intervention immediately, we always have investigate the curability of cancer with secured safety. Disclosure: All authors have declared no conflicts of interest.